Answer:
![s=\sqrt{(3V)/(h)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cwcr4a9o1y4pazgiy838oi7qiindchljnd.png)
Explanation:
We have to re-write the equation and use algebra and solve for s.
This means, we need an expression where it will be "s=SOMETHING".
Lets show the process below:
![V=(1)/(3)s^2 h\\V=(s^2 h)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2ixeemtgaq3wnjk0xi2hswg7ey6gnavvp2.png)
Now we cross multiply and solve for s:
![V=(s^2 h)/(3)\\3V=s^2h\\s^2=(3V)/(h)\\s=\sqrt{(3V)/(h)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/l5m6yxyd3jq9nx88i927pl2p3knkvllkw3.png)
Note: to get s^2 to s, we take square root and eliminate the square
The formula for "s" is:
![s=\sqrt{(3V)/(h)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cwcr4a9o1y4pazgiy838oi7qiindchljnd.png)